Consensus‐based recommendations for the management of rapid cognitive decline due to Alzheimer's disease. Issue 5 (23rd February 2017) - Jia, Jianping; Gauthier, Serge; Pallotta, Sarah; Ji, Yong; Wei, Wenshi; Xiao, Shifu; Peng, Dantao; Guo, Qihao; Wu, Liyong; Chen, Shengdi; Kuang, Weihong; Zhang, Junjian; et al.
Abstract: Introduction: Rapid cognitive decline (RCD) occurs in dementia due to Alzheimer's disease (AD). Methods: Literature review, consensus meetings, and a retrospective chart review of patients with probable AD were conducted. Results: Literature review showed that RCD definitions varied. Mini‐Mental State Examination scores <20 at treatment onset, vascular risk factors, age <70 years at symptom onset, higher education levels, and early appearance of hallucinations, psychosis, or extrapyramidal symptoms are recognized RCD risk factors. Chart review showed that RCD (Mini‐Mental State Examination score decline ≥3 points/year) is more common in moderate (43.2%) than in mild patients (20.1%; P  < .001). Rapid and slow decliners had similar age, gender, and education levels at baseline. Discussion: RCD is sufficiently common to interfere with randomized clinical trials. We propose a 6‐month prerandomization determination of the decline rate or use of an RCD risk score to ensure balanced allocation among treatment groups.